1981
DOI: 10.1149/1.2127341
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Temperature Na Cells: IV . and as Rechargeable Cathodes in Molten

Abstract: Recent work from this laboratory has shown (1-3) that the layered transition metal dichalcogenides which intercalate Na are useful as cathodes for a rechargeable moderate temperature Na cell which operates at 130~ and utilizes 1,2-Bis(2-methoxy-ethoxy)ethane/NaI(iM) as the electrolyte.) unless CC License in place (see abstract). ecsdl.org/site/terms_use address. Redistribution subject to ECS terms of use (see 134.117.10.200 Downloaded on 2015-07-07 to IP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…These include a cell utilizing an acidic NaC1-A1C13 melt with SC13+A1C14 -as the positive electrode (6) and batteries employing a $2C12-A1C13 cathode (5). Our studies of VS~ and MoS3, reported elsewhere (1,3,4), and of NiS and NiS2, presented in this paper, represent first examples of the utility of transition metal sulfide cathodes in molten NaC1-A1C13 electrolyte medium. It would be apparent from the data presented that these results may be of considerable scientific and technological importance.…”
mentioning
confidence: 63%
See 4 more Smart Citations
“…These include a cell utilizing an acidic NaC1-A1C13 melt with SC13+A1C14 -as the positive electrode (6) and batteries employing a $2C12-A1C13 cathode (5). Our studies of VS~ and MoS3, reported elsewhere (1,3,4), and of NiS and NiS2, presented in this paper, represent first examples of the utility of transition metal sulfide cathodes in molten NaC1-A1C13 electrolyte medium. It would be apparent from the data presented that these results may be of considerable scientific and technological importance.…”
mentioning
confidence: 63%
“…Consequently, it is reasonable to assume that the overall electrode process in the cycling of the NiS2 cathode is that in Eq. [3] NiS2 + 4Na + + 4e-+ 2NaA1C]4…”
Section: Moderate Temperature Sodium Cells 2213mentioning
confidence: 99%
See 3 more Smart Citations